Incidence and pathogenesis of megaloblastic erythropoiesis in multiple myeloma. Issue 5 (September 1967) - Hoffbrand, A. V.; Hobbs, J. R.; Kremenchuzky, S.; Mollin, D. L.
Abstract : Intermediate megaloblastic changes occurred in six (19%) of 32 patients with multiple myeloma and trivial megaloblastic changes in a further ten (31%). Folate deficiency was the predominant cause of these changes and in at least two patients was sufficiently severe to contribute to anaemia. Folate deficiency appeared to be due to exćess folate utilization by the tumour and was related to the amount of paraprotein produced daily. Five of the 32 patients had subnormal serum B12 levels. Reduction in the serum B12 level was related to the reduction in the normal circulating immunoglobulins and occurred despite normal B12 absorption. Possible explanations for this finding are discussed.